Career Development Against Employee Performance With Job Satisfaction As Mediation - Jefry Abdul Qory; Mega Asri Zona (Universitas Negeri Padang, 2022)
This study aims to determine the effect of career development on employee performance with job satisfaction as a mediating variable at PT. Perkebunan Nusantara Business Unit Ophir West Pasaman. This research is a causative descriptive research. The population in this study were employees of PT. Perkebunan Nusantara Business Unit Ophir West Pasaman using primary data. The sampling technique used cluster sampling. The number of samples in this study were 60 respondents. The data analysis method used is path analysis on SPSS 23 program assistance. The results show that: (1) career development has a positive and significant effect on employee performance, (2) career development has a positive and significant effect on job satisfaction, (3) job satisfaction has a positive and significant effect on employee performance, (4) career development has a positive and significant effect on employee performance with job satisfaction as a mediating variable.